EVALUATING GAMIFICATION ASSESSMENT IN HIGHER EDUCATION: THE CASE OF QUIZIZZ WITH BLOOM’S TAXONOMY - Abd.Raub, Noor Adila; Md Yunus, Nur Arzilawati; Jamaludin, Nor Lelawati; Ismail, Siti Faridahani; Khadzar, Siti Mursyidah; Abu Bakar, Zamri (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2026)
Educators are increasingly using games to enhance student participation during classes. This study examines the application of Quizizz, a game-based tool in a finance class utilizing Bloom’s Taxonomy framework to collect students’ perceptions regarding its effect on their participation, thinking skills, and learning outcomes. Face-to-face online forms were filled out by thirty-two university undergraduates and analyzed for responses. The general mean results were quite positive at between 4.13 and 4.50 with standard deviations ranging from .81 to 1.07, which means about 90% to 100% of the responses falling in between neutral and positive responses. Students stated that it made them stay alert as well as enhanced their understanding of financial concepts hence more active participation leading also to critical thinking. Such results prove that teachers have an opportunity through assessment design to inspire learners. Game-based learning can make lessons fun and at the same time very challenging. This study may not have covered a large scope but it can help teachers conduct college courses in an interactive manner such that they would also become more effective.